Conservative Management of Placental Abruption - Muhammad Adhitya Wicaksono; Robyanoor Ahyadi; Bambang Abimanyu; Ruth Widhiati; Hermin Sabaruddin (Berkala Kedokteran, 2025)
Placental abruption is a severe obstetric complication. This case involves a 43-year-old woman with chronic hypertension, severe preeclampsia, and IUGR at 26-27 weeks gestation. Underweight (BMI 18.1), she presented with suspected placental abruption, oligohydramnios, and fetal growth restriction. This study highlights the importance of early detection and a multidisciplinary approach in improving outcomes. The patient received conservative treatment, including magnesium sulfate, corticosteroids, antihypertensives, and nutritional support. Despite maternal stability, fetal IUGR, and hypoxia led to an emergency cesarean at 33-34 weeks. A 1055g baby girl was delivered with Apgar scores of 6, 7, and 8. Placental examination revealed retroplacental hemorrhage and calcification. This case emphasizes the importance of early diagnosis, intensive monitoring, and timely intervention in high-risk pregnancies with placental abruption and severe preeclampsia. A multidisciplinary approach is essential to improve maternal and neonatal prognosis.